18F‐Fluorodeoxyglucose positron emission tomography can be used to determine the indication for endoscopic resection of superficial esophageal cancer. (28th June 2018) - Nakajima, Masanobu; Muroi, Hiroto; Yokoyama, Haruka; Kikuchi, Maiko; Yamaguchi, Satoru; Sasaki, Kinro; Kato, Hiroyuki
Abstract: 18 F‐Fluorodeoxyglucose positron emission tomography (FDG‐PET) is a useful imaging modality that reflects the tumor activity. However, FDG‐PET is mainly used for advanced cancer, not superficial cancer. In this study, we investigated the relationship between the superficial tumor depth of esophageal cancer and the FDG uptake to determine the indications for endoscopic resection (ER). From 2009 to 2017, 444 patients with esophageal cancer underwent esophagectomy or endoscopic submucosal dissection (ESD), and 195 patients were pathologically diagnosed with superficial cancer. Among them, 146 patients were examined by FDG‐PET before esophagectomy or ESD. In these 146 patients, the relationship between the pathological tumor depth and FDG uptake was analyzed. The mean maximum standardized uptake value in pT1a‐EP/LPM tumors was 1.362 ± 0.890, that in pT1a‐MM/pT1b‐SM1 tumors was 2.453 ± 1.872, and that in pT1b‐SM2/SM3 tumors was 4.265 ± 3.233 ( P  <   .0001). Among 51 pT1a‐EP/LPM tumors, 10 (19.6%) showed positive detection of FDG. For pT1a‐MM/pT1b‐SM1 and pT1b‐SM2/SM3 tumors, the detection rate was 52.9% (18/34) and 82.0% (50/61), respectively. The detection rate of pT1a‐EP/LPM was significantly lower than in the other two groups ( P  <   .0001). Among 10 FDG‐PET‐positive lesions, only 1 had no apparent reason for PET positivity; however, 9 of 10 had a suitable reason for detectability by PET and inadequacy for ER. Negative detection of superficial esophageal squamous cell carcinoma by FDG‐PET is useful to determine the indication for ER when the tumor depth cannot be diagnosed even after performing magnifying endoscopy with narrow band imaging and endoscopic ultrasonography. When FDG uptake is recognized, a therapeutic modality other than ER should be considered. Abstract : Superficial esophageal SCC, which is excisional by ER, is not usually detectable by FDG‐PET. If FDG uptake is recognized in superficial esophageal SCC, a therapeutic modality other than ER should be considered.